Pencegahan Healthcare Associated Infections Melalui Kepatuhan Perawat dalam Hand Hygiene - Moecharam, Moecharam; Nursalam, Nursalam; Ahsan, Ahsan (Universitas Muhammadiyah Surabaya, 2021)
Introduction: Hand hygiene is a simple, effective step in reducing infection rates, but is often forgotten by healthcare workers. Low hand hygiene in health workers is influenced by several factors, namely: ignorance of health workers about how hands can be contaminated and ignorance of the importance of hand hygiene in reducing the spread of infection. This study aims to explore clinical nurse counselors in hand hygiene. Method: This study used a qualitative study design with a phenomenological approach. This study involved 15 clinical nurse nurses who conducted in-depth interviews using semi-structured interview guidelines with inclusion criteria: aged 25 - 45 years, became clinical advisors in the room, working period> 8 years. Data from indepht interview results were transcribed and analyzed data using the Van Mannen analysis method. Results: Three themes were identified in this study, namely: 1) Hand hygiene knowledge, knowledge of hand hygiene is based on: an understanding of germ transmission, so that nurses are able to prevent transmission and accompanied by regulations from the implementation of hand hygiene that guide the implementation. 2) Social support, social support implementing hand hygiene arises from coworkers who provide support ranging from frequent reminders, conducting supervision to preparation of alcohol hand rub facilities on each patient's bed. and 3) Behavior, manifested compliance with hand hygiene for nurses in the prevention of HAIs by increasing personal and social routines as reflected in behavior in the prevention of HAIs. Conclusion: Clinical nurse in hand hygiene is based on knowledge, social support and behavior in implementing hand hygiene. The implication of the results of this study is information in an effort to improve compliance with hand hygiene so that meeting health needs is not only focused on meeting the needs of patients but also taking into account the risk of germ transmission.